The Effect of Carriage of CYP3A5*3 and CYP3A4*22 Polymorphic Variants on the Safety of Remdesivir Therapy in Patients with COVID-19 - I. I. TEMIRBULATOV; A. V. KRYUKOV; K. B. MIRZAEV; N. P. DENISENKO; S. P. ABDULLAEV; A. S. ZHIRYAKOVA; Y. V. SHEVCHUK; V. I. VECHORKO; O. V. AVERKOV; D. A. SYCHEV (Антибиотики и Химиотерапия, 2022)
The aim of the study was to assess the association of polymorphic variants CYP3A5*3 6986 A>G rs776746 and CYP3A4*22 rs35599367 C>T with the safety parameters of remdesivir therapy in patients with COVID-19.Material and methods. The study included 156 patients admitted to the City Clinical Hospital No. 15 of the Moscow Health Department with COVID-19 diagnosis, who received remdesivir as an antiviral drug. The frequency of adverse reactions (bradycardia, dyspeptic disorders), as well as various laboratory parameters (ALT, AST, creatinine, ferritin, interleukin-6, and d-dimer levels) were compared between the carriers of wild-type and polymorphic variants of the studied genes.Results. Carriers of CYP3A5*3 polymorphic variants (GA+AA) had higher ALT levels after the treatment with remdesivir than carriers of the wild variant (GG). When comparing the level of interleukin-6 after therapy with remdesivir, carriers of the polymorphic variant of the CYP3A4*22 (CT) gene had a significantly higher level of this cytokine.Conclusion. An association between the carriage of polymorphic variants of CYP3A5*3 and an increase in the level of liver enzymes was found. Polymorphic variants of CYP3A4*22 were associated with higher levels of interleukin-6. Additional pharmacogenetic studies are required to assess the possibilities of personalizing antiviral therapy for COVID-19.